2019
DOI: 10.1021/acs.energyfuels.9b01640
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Sequence of Acetalization and Hydrogenation for Synthesis of Diesel Fuel Additives from Furfural and Diols

Abstract: Acetalization of diols with furfural and subsequent hydrogenation of acetal products provided potential fuel additives that could be blended into commercial diesel. Glycerol could be an interesting polyol for acetalization with furfural due to its low cost, and it is produced as a byproduct in very large amount in the process of biodiesel production. In this work, glycerol acetalization with furfural has been selected as a model reaction. Acetalization reaction was performed under neat conditions (solventless)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…A rhenium-containing hectorite ReHectMw used in catalyst/Gly = 0.05 (entry 11 [101]) led to 23% total acetals yield at 40 • C/4 h, and 1 in a fifth of the catalyst/Gly ratio led to 37% total yield at 50 • C/0.5 h. Very good results were reported for Zr-Montmorillonite (entry 9 [106]), 12-tungstosilicic acid supported on MCM-48 (TSA-nMCM-48, entry 15 [113]) and a sulfonic acid functionalized organic polymer (An-POP-SO 3 H, entry 20 [84]), used in a catalyst/Gly ratio between 0.02 and 0.2, which led to 78-87% total acetals yield in the temperature range room temperature (rt)-40 • C and 0.5-4 h reaction time. Similar results (78-91% total yield) were reached for 1 with catalyst/Gly = 0.01-0.1, albeit at 90 • C/4 h (entries 5, 6).…”
Section: Reaction Of Furfural and Glycerol To Heterobicyclic Productsmentioning
confidence: 93%
See 3 more Smart Citations
“…A rhenium-containing hectorite ReHectMw used in catalyst/Gly = 0.05 (entry 11 [101]) led to 23% total acetals yield at 40 • C/4 h, and 1 in a fifth of the catalyst/Gly ratio led to 37% total yield at 50 • C/0.5 h. Very good results were reported for Zr-Montmorillonite (entry 9 [106]), 12-tungstosilicic acid supported on MCM-48 (TSA-nMCM-48, entry 15 [113]) and a sulfonic acid functionalized organic polymer (An-POP-SO 3 H, entry 20 [84]), used in a catalyst/Gly ratio between 0.02 and 0.2, which led to 78-87% total acetals yield in the temperature range room temperature (rt)-40 • C and 0.5-4 h reaction time. Similar results (78-91% total yield) were reached for 1 with catalyst/Gly = 0.01-0.1, albeit at 90 • C/4 h (entries 5, 6).…”
Section: Reaction Of Furfural and Glycerol To Heterobicyclic Productsmentioning
confidence: 93%
“…Protonic lignosulfonate-based macro/mesoporous 80LS 20 PS 450 H + (synthesized in a multistep fashion involving freeze-dry, pyrolysis, ion exchange) was tested for the Fur/Gly reaction at 100 • C/1 h (entry 23 [103]), leading to similar results to 1 at 90 • C/4 h, in a higher catalyst:Gly ratio (entry 6), 93% and 91% total acetals yield, respectively. The performance of 1 seemed somewhat comparable/superior to the acid resins Amberlyst-15 (80% total yield at 70 • C/4 h, cyclohexane as co-solvent, entry 21 [77], compared to 81% for 1 at 70 • C/4 h without cosolvent, entry 4) and Amberlite-IR120 (56% total yield at rt/4 h, entry 22 [106], compared to 56% for 1 used in a sixth of the catalyst/Gly mass ratio at 50 • C/2 h, entry 1). Overall, the catalytic results for 1 in the Fur/Gly reaction seemed relatively good among the studied solid acid catalysts.…”
Section: Reaction Of Furfural and Glycerol To Heterobicyclic Productsmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, acetals derived from furfural and polyols such as propylene glycol and glycerol are considered as potential biofuels and fuel precursors. [11] For the acetalization reactions of furfural and short-chain alcohols, it was usually required high reaction temperature (60-140°C) for pure Lewis acid catalysts, such as NiÀ Al LDH, [12] NiRh/ γ-Al 2 O 3 [13] and titanium suboxide Ti 2 O 3 , [14] whereas room temperature was enough for the Brønsted acid catalysts such as sulfonic cation exchange resin, H 2 SO 4 , HCl, p-toluenesulfonic acid, H 3 PW 12 O 40 , and H 3 PMo 12 O 40 , [10b,15] indicating Lewis acid and Brønsted acid are the two driving forces that can act independently to accelerate the acetalization reactions. Furthermore, it was revealed that the catalytic performance of the catalysts with both Brønsted acid (strong or weak) sites and hard Lewis acid sites was better than that of pure Brønsted acid catalysts.…”
Section: Introductionmentioning
confidence: 99%